Discussions about modern architecture in the «Architecture and construction of Uzbekistan» magazine: the evolution of treatments and interpretations - Polyakov Grigory M. (Архитектон, 2025)
The article discusses the evolution of interpretations of "modern architecture" in Uzbekistan of the Soviet period in the journal “Architecture and Construction of Uzbekistan” (1955-1992) over three decades from the 1960s to the end of the Soviet era in the 1980s. Key stages in the transformation of ideas concerning "modern architecture" are illustrated by publications of significant architects and researchers from Soviet Uzbekistan. Consideration is given to the characteristics of architectural practice in each period, including interpretations of common Soviet policies by Uzbek architects, architectural projects from the countries of the Global South, and Uzbek architectural trends.